(untitled) (Research, Society and Development, 2023)
Objective: This research aimed to evaluate the antimicrobial activity of hydroalcoholic extracts of Allium schoenoprasum against Staphylococcus aureus and Escherichia coli in vitro. Methodology: The hydroalcoholic extract of A. schoenoprasum was prepared using 70% alcohol, then different extract concentrations (1, 10 and 100 µg/mL) were incubated with S. aureus and E. coli in BHI broth for 48 hours, and bacterial growth was evaluated by spectrophotometry. Results: It was observed that the concentrations of 10 and 100 µg/mL of the extract were able to inhibit the growth of S. aureus and E. coli bacteria after 48 hours when compared to the control. Conclusion: The extract of A. Schoenoprasum can inhibit the growth of E. coli and S. aureus in vitro, which may be due to substances present in the leaves of the plant, such as tannins and phenolic compounds, however, future studies may verify the toxicity of the extract in host cells and even understand the mechanism of action of antimicrobial activity.